ANALISIS EVALUASI KINERJA PERAWAT DALAM MENINGKATKAN PELAYANAN KESEHATAN PADA UPTD PUSKESMAS AWAAI KECAMATAN SITOLU ORI KABUPATEN NIAS UTARA - Ziliwu, Lisnawati; Zega, Yamolala; Mendrofa, Martha Surya Dinata; Zai, Kurniawan Sarototonafo (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2025)
This study aims to analyze the evaluation of employee performance and public services at PT. Permodalan Nasional Madani Mekar, Nias Regency. The main focus of the study is how employee performance can affect the improvement of the quality of public services provided to the community. By using qualitative methods, data were obtained through field interviews with informants from various levels in the company. The results of the study showed that although employee performance in general was good, there were still several aspects that needed improvement, especially in terms of service speed and customer assistance. In addition, more routine and intensive evaluations were needed to maintain consistent service quality. In terms of public services, PT. PNM Mekar has shown a high commitment, but there is still room to improve effectiveness and efficiency in handling customer needs. Based on the results of interviews with the informants above, it can be explained that the competence of PT. PNM Mekar officers in serving customers is already at an adequate level. However, further improvements, especially in terms of understanding customer needs in depth and continuous training, can help improve service quality and provide a greater positive impact on the community.